Pedagogical Competencies of Pre-Service Teacher Professional Education in Understanding and Implementing the Teaching at the Right Level (TaRL) Approach - Abidin, Zainal; Setiawan, Yayan Eryk; Alifiani, Alifiani; Widodo, Ganjar Setyo; Siswiyanti, Frida (Jurnal Pendidikan Progresif, 2024)
Abstract: Pedagogical Competencies of Pre-Service Teacher Professional Education in Understanding and Implementing the Teaching at the Right Level (TaRL) Approach. Objective: The objective of this research to describe students' understanding of TaRL and their ability to implement the TaRL approach at school. Methods: This type of research is quantitative survey research. This research was carried out at the Islamic University of Malang with the research population being TPE Pre-service students class 1. The sample for this research was 71 students, all of whom were taken from the research population. The data collected in this research is in the form of the results of filling out a questionnaire. The questionnaire used in this research is valid and reliable. Next, the data obtained was analysed descriptively. Findings: The results of the research show that the average student understanding of the TaRL approach is 4.50 and the average ability to apply TaRL in learning is 4.15, which means the understanding and implementation of the TaRL approach is in the very good category. Conclusion: From the research results, it can be concluded that students can understand the TaRL approach well and can apply it in learning at school. Recommendations for further research are analysing the obstacles and solutions made by students in implementing the TaRL approach. Keywords: pedagogical competency, TPE, TaRL approach, differentiated learning.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202434